Analisis Kesalahan Berbahasa Mandarin dalam Karangan Deskriptif dan Argumentatif pada Keterampilan Menulis Tingkat Lanjut - Aditya, Rendy; Wikarti, Aprilia Ruby; Wardhani, Rizky; Prasetyaningtyas, Hudiyekti; Legitah, Sagitah Ningrum; Syafira, Ratu Rina; Yili, Zhu; Qiyu, Zhang (Universitas Muhammadiyah Magelang, 2026)
Based on the research findings, it can be concluded that the implementation of the Outcome-Based Education (OBE) curriculum in the Advanced Mandarin Reading and Writing II course at the Mandarin Language Education Study Program, State University of Jakarta, has made a positive contribution to the development of students’ writing skills. Through the application of Self-Directed Learning and Project-Based Learning methods, students are able to produce written works in the form of descriptive and argumentative essays in Mandarin that meet the competency standards of HSK Level 4. This study employs a qualitative approach by describing the results of language error analysis on descriptive and argumentative essays produced by students in the Advanced Mandarin Reading and Writing II course. The data sources of this research are descriptive and argumentative essays written by 10 students. The data in this study are the types of errors found in the students’ essays, totaling 110 essays in Mandarin. The research found two types of language errors in the students’ descriptive and argumentative essays in Mandarin: syntactic errors and lexical errors. Syntactic errors include mistakes in word usage, grammatical errors, and inaccuracies in word choice. Meanwhile, lexical errors include incorrect writing of Han characters and improper use of words with similar meanings. These errors are generally caused by students’ limited understanding of the meaning of Mandarin vocabulary and mistakes in writing or typing Han characters. Therefore, increased practice in Mandarin writing skills is needed, particularly in mastering grammatical structures, using appropriate vocabulary, and accuracy in writing Han characters, so that students’ writing abilities can develop optimally.